A HYBRID ARIMA POLYNOMIAL HARMONIC GMDH MODEL TO FORECAST CRUDE OIL PRICE - YAW SARPONG-STREETOR, RICHARD MANU NANA (2019)
Crude oil and its’ extracts supply 33% of all the energy consumed worldwide, thus it plays a critical role in affecting the world’s economy. The crude oil price has generally risen over the years, post-world war II, it has been influenced by demand and supply. Several other factors such as Organization of the Petroleum Countries (OPEC) basket reference price policies, wars, political instability, improved or macro-economic conditions in some geo-political areas such as Asia and crashing global financial crises have had effects on the crude oil price. The time series of crude oil price is non-linear and irregular thus forecasting crude oil price has become very difficult. Crude oil price fluctuations are of significant interest to most individuals and organizations on the globe. Forecasting is a major step to hedge against crude oil price fluctuations. Several attempts have been made by researchers to forecast crude oil price accurately by using various forecasting techniques such as quantitative or qualitative methods.